2021
DOI: 10.1167/jov.21.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of complex stimuli across saccades

Abstract: The visual system can predict visual features across saccades based on learned transsaccadic associations between peripheral and foveal input. This has been shown for simple visual features such as shape, size, and spatial frequency. The present study investigated whether transsaccadic predictions are also made for more complex visual stimuli. In an acquisition phase, new transsaccadic associations were established. In the first experiment, pictures of real-world objects changed category during the saccade (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…Experimentally, it has been shown that, after being exposed to new transsaccadic object changes, peripheral perception is biased in the direction of the learned transsaccadic associations. This effect has been shown in various studies and with multiple object features ( Herwig & Schneider, 2014 ; Köller, Poth, & Herwig, 2020 ; Osterbrink & Herwig, 2021 ; Paeye, Collins, Cavanagh, & Herwig, 2018 ; Valsecchi & Gegenfurtner, 2016 ). One aspect that is not clear yet though, and that has also been pointed out as an open question in the review article by Stewart, Valsecchi, and Schütz (2020) is the location specificity of this learning process, because two studies that will be described in more detail hereafter have shown seemingly contradictory findings.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Experimentally, it has been shown that, after being exposed to new transsaccadic object changes, peripheral perception is biased in the direction of the learned transsaccadic associations. This effect has been shown in various studies and with multiple object features ( Herwig & Schneider, 2014 ; Köller, Poth, & Herwig, 2020 ; Osterbrink & Herwig, 2021 ; Paeye, Collins, Cavanagh, & Herwig, 2018 ; Valsecchi & Gegenfurtner, 2016 ). One aspect that is not clear yet though, and that has also been pointed out as an open question in the review article by Stewart, Valsecchi, and Schütz (2020) is the location specificity of this learning process, because two studies that will be described in more detail hereafter have shown seemingly contradictory findings.…”
Section: Introductionsupporting
confidence: 53%
“…A learning index was computed as a measure for the presaccadic perceptual bias, thus for the effect of the transsaccadic learning on the presaccadic shape judgments ( Herwig & Schneider, 2014 ; Osterbrink & Herwig, 2021 ; Paeye et al, 2018 ). For this, the average shape judgment of the swapped object was subtracted from the shape judgment of the normal object in the circle-to-square group, and the normal shape judgment was subtracted from the swapped shape judgment in the square-to-circle group.…”
Section: Resultsmentioning
confidence: 99%
“…That is, had the object’s frequency changed from low to high, they perceived the peripheral frequency higher than that of a baseline object whose frequency did not change during the acquisition phase. This object-specific, presaccadic perceptual bias has been shown in several studies and feature dimensions such as spatial frequency (Herwig et al, 2018; Herwig & Schneider, 2014), shape (Herwig et al, 2015; Köller et al, 2020; Paeye et al, 2018), size (Bosco et al, 2015, 2020; Valsecchi et al, 2020; Valsecchi & Gegenfurtner, 2016) and even more complex stimulus dimensions like the gender of a face (Osterbrink & Herwig, 2021).…”
Section: Transsaccadic Integrationmentioning
confidence: 60%
“…There were no manipulations of reliability included in this experiment. Similar to earlier studies investigating the presaccadic perceptual bias (e.g., Herwig & Schneider, 2014; Osterbrink & Herwig, 2021) we expected participants to show biases in their peripheral perception of features in the object type that was changed during acquisition.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation